New Metropolitan Perspectives Transition with Resilience for Evolutionary Development - Bevilacqua, Carmelina; Balland, Pierre-Alexandre; Kakderi, Christina; Provenzano, Vincenzo (Lecture Notes in Networks and Systems, 2023)
This open access book conveys attention to the theme of transition towards resilience and sustainability and its evolutionary perspective that emphasizes the complexity and uncertainty that governments and society are called to address in response to the ongoing challenges. "New Metropolitan Perspective Post COVID Dynamics: Green and Digital Transition, between Metropolitan and Return to Villages' Perspectives", 25-27 May 2022, Reggio Calabria, Italy. The papers included in the book are grouped around the following main topics: the envisaged transition towards resilience and sustainability; the relevance of the planning dimension for defining sustainable development pathways and managing complexity; and the green and digital transition by glimpsing at approaches, experiences, and cases that outline innovative solutions in cities and inner areas. The book primarily targets the academic and policymaker communities involved in managing the complexity of the transition for regions and cities.